Pemakaian Antibiotika Pada Pengobatan TifoidPasien Rawat Inap Dewasa Di Satu Rumah Sakit UmumDan Rumah Sakit Swasta Di Jawa Tengah Tahun 2002 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Thyphoid is still endemic disease in Indonesia and the critical issue is antibiotic usage for thyphoid therapy. The study was conducted in one of governmental and private hospital in Central Java in 2002 and the aim of the research was to describe antibiotic usage. The study was done by using non experimental design and retrospective methods. Medical records as source of data was analysed using non analytical descriptive compared with therapeutics standard from National Medical Association. The result shown there were polypharmacy in antibiotic usage in governmental hospital 44.2% and 24.6% in private hospital respectively. Antibiotic that was inappropriate for thyphoid used in both hospital were gentamicyne, amikacyne, metronidazole and limkomycine. Keywords: thypoid, antibiotic, polypharmacy